Imbas Kemasan dan Citra Merek Dalam Keputusan Pembelian Produk UMKM Khas Lampung - Muhammad Junaidi; Anisa Martiah; Deddy Sulaimawan; Ketut Partayasa (Komunitas Dosen Indonesia, 2023)
The food business has recently become something interesting and promising to do, work, creativity and research. Currently, the snack business is experiencing rapid growth, both on a national scale and on a small and medium business scale. The aim of this research is to analyze how much influence packaging and brand image have on purchasing decisions for MSME products. The research was conducted at Ibu Rina's Cassava Chip Business, which is located in Labuhan Ratu Dua Village, in the East Lampung area. The population is consumers of cassava chips made by Mrs. Rina. Sample data was obtained and collected using cluster sampling and incidental sampling techniques. The collected data using questionnaires was investigated and tested using the multiple linear regression formula using the SPSS program. Tests carried out indicate that the packaging has a positive impact. Mrs. Rina's purchase of cassava chips was not significantly influenced by brand image. Purchasing decisions are significantly influenced by packaging and brand image simultaneously. The hope is that this research will provide concrete and academic uses